Gambaran Pencabutan Gigi di Rumah Sakit Gigi dan Mulut (RSGM) Universitas Andalas Pasca Pandemi Covid-19 - Surma Adnan; Tiara Adzakiyah (Andalas Dental Journal, 2022)
Background: Tooth extraction in dentistry is an act of removing the tooth from the socket hole in the alveolar bone, where there is no more treatment that can be done to maintain the tooth. Tooth extraction is one of the recruitment cases to complete dental studies at the Faculty of Dentistry, Andalas University. Purpose: to examine the prevalence of tooth extraction and its distribution based on gender, age, and causal factors after the COVID-19 pandemic at the Dental and Oral Hospital (RSGM) Faculty of Dentistry, Andalas University. Method: This type of research is descriptive research with a retrospective design. The sampling technique used is purposive sampling and the number of samples obtained is 649 samples. Results: The prevalence of tooth extraction was 16.3%. Based on gender, 366 cases (56.4%) of women had their teeth extracted, which was higher than 283 cases of men (43.6%). Most tooth extractions were recorded in the age group 1-10 as many as 253 cases (39%). The most common causal factor of tooth extraction was retained dental root in 195 cases (30%) Conclusion: .The prevalence of tooth extraction in the RSGM, Universitas Andalas still high, so an adequate education and prevention of tooth extraction was highly recommended to the society.